Relationships between learning organization dimensions and organizational commitment as perceived by lecturers in technical and vocational colleges in Iran - Nazari, Khosrow (2012)
The study was an attempt to explore relationships between learning organization and organizational commitment among lecturers in Technical and Vocational Colleges (TVCs) in Iran. Watkins and Marsick‟s (1993) learning organization model with associated questionnaire; Learning Organization Dimensions Questionnaire (LODQ)was employed to collect data to determine lecturers‟ perception on learning organization dimensions. Allen and Meyer‟s (1996) tridimensional model of organizational commitment with associated questionnaire; Organizational Commitment Questionnaire (OCQ) was also utilized to collect data and determine lecturers‟ perception on organizational commitment. The study was designed to determine levels of learning organization dimensions, organizational commitment scale and subscales, differences in respondents‟ perception based on selected demographic variables (age, gender, marital status, teaching experience, employment type, level of education, and monthly income), relationship between learning organization dimensions and organizational commitment and significant predictors of affective, continuance, normative and overall organizational commitment. The research design was descriptive correlational study and data were collected employing questionnaires. The study utilized proportional and simple random sampling methods to select 295 respondents with the response rate of 95.16% from population in four provinces of Fars, Khouzestan, Boushehr, and Kohgiloya and Boyerahmad in Iran. The findings showed that lecturers‟ perception on learning organization was at moderate level. Out of seven learning organization dimensions, three dimensions of continuous learning, dialogue and inquiry and strategic leadership were rated at high level, and four dimensions of collaboration, embedded system, system connection, and empowerment were rated at moderate level. Level of lecturers‟ perception in overall organizational commitment was found to be at moderate level, affective commitment at high level, whereas continuance and normative commitment were rated at moderate level. Differences in affective, continuance, normative and overall organizational commitment by demographics showed that lecturers who were full time, had doctorate degree, were in the age of 50 and more, and had more than $ 800 monthly income had higher affective, continuance,normative and overall organizational commitment than their counterparts. Positive, significant and small to high relationships were found to exist between learning organization dimensions and organizational commitment scale and subscales. Overall correlation between learning organization dimensions and organizational commitment showed to be high, and positive. All seven learning organization dimensions were found to be predictors of organizational commitment,except collaboration. Significant predictors including continuous learning, dialogue and inquiry, embedded system, empowerment, system connection and strategic leadership accounted for 50.3% of variance in overall organizational commitment. It is recommended that to improve organizational commitment scale and subscales, TVCs leaders should develop and practice learning organization dimensions especially three dimensions of dialogue and inquiry, continuous learning and strategic leadership and associated practices. A human resource development system should also be created to promote a learning culture based on learning organization dimensions and at the same time, to develop, maintain and enhance organizational commitment scale and subscales.